2019
DOI: 10.1021/acs.nanolett.9b01264
|View full text |Cite
|
Sign up to set email alerts
|

Control of Conductivity of InxGa1–xAs Nanowires by Applied Tension and Surface States

Abstract: The electronic properties of semiconductor AIIIBV nanowires (NWs) due to their high surface/volume ratio can be effectively controlled by NW strain and surface electronic states. We study the effect of applied tension on the conductivity of wurtzite In x Ga 1−x As (x ∼ 0.8) NWs. Experimentally, conductive atomic force microscopy is used to measure the I−V curves of vertically standing NWs covered by native oxide. To apply tension, the microscope probe touching the NW side is shifted laterally to produce a tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Recently, it was shown that the Fermi level in III-As semiconductors was pinned due to the formation of excess surface arsenic at the oxidized or metalized surface [45]. The position of pinning (effective work function) was~4.8 eV for n-type and~4.95 eV for p-type semiconductors, implying insensitivity to mechanical deformation [46,47]. During modeling, the work function of the contact was set at Φ eff n = 4.8 and Φ eff p = 4.95 eV for n-type and p-type GaAs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that the Fermi level in III-As semiconductors was pinned due to the formation of excess surface arsenic at the oxidized or metalized surface [45]. The position of pinning (effective work function) was~4.8 eV for n-type and~4.95 eV for p-type semiconductors, implying insensitivity to mechanical deformation [46,47]. During modeling, the work function of the contact was set at Φ eff n = 4.8 and Φ eff p = 4.95 eV for n-type and p-type GaAs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Schottky barrier between semiconductor and metal electrode can reduce the dark current of photodetectors. [18,[27][28][29] Beyond surface passivation, the construction of core-shell NWs and the introduction of stress, etc., [30][31][32][33][34] surface decoration is becoming a popular approach to control the surface Fermi level pinning effect of semiconductors' NWs. [35] With decoration, the carriers will transfer at the interfaces between NWs and decorated semiconductors, The surface Fermi level pinning effect promotes the formation of metalindependent Ohmic contacts for the high-speed GaSb nanowires (NWs) electronic devices, however, it limits next-generation optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…High deformation stability of NWs allows to control their electronic and optoelectronic properties by elastic strains. Particularly, for III-As (InAs, GaAs, InGaAs) NWs a 2% mechanical deformation was shown to redshift the photoluminescence position by 290 meV [7] or change NW conductivity by four orders of magnitude [8,9]. Non-zero piezoelectric coefficients along the NW growth axis (111) in zinc-blende (ZB) and wurtzite (WZ) NWs allow enhancing characteristics of sensors [10], light-emitting diodes [11], ambient mechanical energy harvesters [5,12], photodetectors [13,14], and solar cells [15].…”
Section: Introductionmentioning
confidence: 99%